ANALISIS SHOPPING LIFESTYLE & FASHION INVOLVEMENT TERHADAP IMPULSE BUYING (Studi Kasus Pembelian Kaos Pada Mahasiswa Politeknik Cendana) - Anggraini, Dewi; Ferayani, Ferayani; Williny, Williny; Nugroho, Ngadjudin; Arif, Anggia (Jurnal Kajian Ekonomi dan Kebijakan Publik (JEpa); Vol 7 No 2 (2022): Jurnal Kajian Ekonomi dan Kebijakan Publik (JEpa), 2022)
This study aims to assess the Effect of Shopping Lifestyle and Fashion Involvement on Impulse Buying (Case Study of Buying T-shirts at Cendana Polytechnic Students). The type of research used in this research is descriptive quantitative research. The processed data is the result of distributing questionnaires to students of the Management Study Program at the Cendana Polytechnic. The sampling method is non-probability sampling and the technique used in taking respondents is accidental sampling. The data analysis technique used in this research is multiple linear regression. Based on the results of data analysis, it can be concluded that Shopping Lifestyle has a positive and significant effect on Impulse Buying, as well as Fashion Involvement has a positive and significant impact on Impulse Buying of T-shirt Purchases for Cendana Polytechnic Students.